Analisis Kepentingan Nasional Uni Emirat Arab Dalam Normalisasi Hubungan Dengan Israel - A Rizki Tahmi; Mohamad Rosyidin; Muhammad Faiza; Alfian (Journal of International Relations Diponegoro, 2022)
The normalization of diplomatic relations between the UAE and Israel in 2020 is an event that has shocked the international community. As we know that the UAE and Israel have a not good history in international relations. Therefore, the normalization of relations is a big step for the foreign policy of the two countries. The normalization of diplomatic relations between the UAE and Israel gave birth to an agreement known as the Abraham Accords. This agreement is the basis for relations between the two countries which contains points of cooperation that will be carried out. The change in policy made by the UAE in normalizing this relationship is a characteristic aspect of global political dynamics. The UAE's national interest is one of the factors considered the reason for the normalization of diplomatic relations to occur. So the purpose of this study is to analyze the UAE's national interest in normalizing relations with Israel and the level of urgency of these interests. This research will use the National Interest Concept in the form of a National Interest Matrix. Based on the research conducted, the main argument of the author is that the normalization of diplomatic relations carried out by the UAE with Israel cannot be separated from the national interests of the UAE.